Explaining the variation in historical trends for agriculture and population density using soil, climate, and topography data. A case study from Denmark. Issue 2 (3rd July 2021) - Roell, Yannik E.; Jacobsen, Niels M.; Graversgaard, Morten; Lohrum, Nele; Beucher, Amélie; Greve, Mette B.; Greve, Mogens H.; Kjeldsen, Chris
ABSTRACT: Agricultural land use and population density have been increasing around the world. Determining if physical geography is a driving factor of historical change on a larger scale has received little research interest in the past outside local-scale case studies. The aim of this study was to model historical agricultural development and population density throughout Denmark using geographically weighted regression with environmental variables and data for parishes from 1860 to 1890. We analysed rye production, sheep count, and population density on the national scale. The incorporated variables were selected to represent aspects of soil, climate, and topography. Models for rye and sheep had high explanatory power (global R 2 : between 0.60 and 0.68) for both time periods whereas the model for population density had low explanatory power (global R 2 : 0.09 in 1860 and 0.25 in 1890). The results indicate that historical development in agricultural geography can be explained using physical geography. However, population density is more complex due to influences of industrialization, culture and scalar structure. This questions the classical understanding that soil quality is a strong determinant of population density on its own in Denmark. We instead argue that soil quality has a dynamic multidirectional interplay with human and agricultural activity.